2018
DOI: 10.1177/2045893217749987
|View full text |Cite
|
Sign up to set email alerts
|

Protective role of FKBP51 in calcium entry‐induced endothelial barrier disruption

Abstract: Pulmonary artery endothelial cells (PAECs) express a cation current, ISOC (store-operated calcium entry current), which when activated permits calcium entry leading to inter-endothelial cell gap formation. The large molecular weight immunophilin FKBP51 inhibits ISOC but not other calcium entry pathways in PAECs. However, it is unknown whether FKBP51-mediated inhibition of ISOC is sufficient to protect the endothelial barrier from calcium entry-induced disruption. The major objective of this study was to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(26 citation statements)
references
References 57 publications
3
23
0
Order By: Relevance
“…In doxycycline‐treated cells, with increased FKBP51 expression, I SOC was decreased by ~52% (~14 pA at −80 mV) with no change in reversal potential. Indeed, this result is consistent with our previous observations in rat PAECs . Finally, using doxycycline‐inducible FKBP51 over‐expressing cells, we wanted to determine whether upregulation of FKBP51 in PMVECs protects the endothelial barrier, as it does in PAECs .…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…In doxycycline‐treated cells, with increased FKBP51 expression, I SOC was decreased by ~52% (~14 pA at −80 mV) with no change in reversal potential. Indeed, this result is consistent with our previous observations in rat PAECs . Finally, using doxycycline‐inducible FKBP51 over‐expressing cells, we wanted to determine whether upregulation of FKBP51 in PMVECs protects the endothelial barrier, as it does in PAECs .…”
Section: Resultssupporting
confidence: 89%
“…We first observed that upregulation of the PPP5C‐FKBP51 axis inhibits I SOC in PMVECs. As this observation supports our earlier data in PAECs, it suggests that inhibition of I SOC by the PPP5C‐FKBP51 axis is a fundamental mechanism in endothelial cells. Second, we found that S100A6 is required for the PPP5C‐FKBP51‐mediated inhibition of I SOC , working through the PPP5C arm of the axis.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Other FKBPs may also be the target of the drugs. FKBP51 and FKBP52 regulate steroid receptor signalling and store operated Ca 2+ entry and some TRP channels (Hamilton et al, 2018;Kadeba et al, 2013;Sinkins, Goel, Estacion, & Schilling, 2004) to modulate cell function. The present findings suggest that rapamycin and FKBP do not modulate Ca 2+ release.…”
Section: Discussionmentioning
confidence: 99%